2022
DOI: 10.1039/d1en01004b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polystyrene nanoplastics on the bioaccumulation, distribution and parental transfer of ethylhexyl salicylate

Abstract: In this study, the accumulation and distribution of ethylhexyl salicylate (EHS) and polystyrene nanoplastics (PS-NPs) in parental zebrafish (Danio Rerio) and offspring, and the effects of PS-NPs on EHS bioavailability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The presence of nine pharmaceuticals in the gonadal indicates that these pharmaceuticals could cross the blood–ovary barrier and increase the risk of transgenerational toxicity. Zhou et al [ 35 ] found that the distribution of ethylhexyl salicylate in gonads could be transferred to offspring through reproduction, thus influencing its growth, development, and locomotor vitality. In addition, the muscle also had a high concentration of pharmaceuticals.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of nine pharmaceuticals in the gonadal indicates that these pharmaceuticals could cross the blood–ovary barrier and increase the risk of transgenerational toxicity. Zhou et al [ 35 ] found that the distribution of ethylhexyl salicylate in gonads could be transferred to offspring through reproduction, thus influencing its growth, development, and locomotor vitality. In addition, the muscle also had a high concentration of pharmaceuticals.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies have previously detected the presence of contaminants, such as persistent organic pollutants and nanoparticles, in the brains of zebrafish larvae exposed to exogenous contaminants, suggesting that all of the above substances can enter the CNS through the blood-brain barrier. Contaminants entering the brain can induce neurotoxicity at the cellular and molecular levels through oxidative stress or inflammatory responses (Lu et al, 2016;Zhou et al, 2022b), which could be the reason for the apoptosis induced by BM-BDM and 100 nm PS-NPs in this experiment.…”
Section: Apoptosis and Expression Of Apoptosisrelated Genes In The Cn...mentioning
confidence: 90%
“…Butyl methoxydibenzoyl methane (BM-DBM) is one of the main occurrences of OUVFs in the environment, whose levels in surface water (Rodriguez et al, 2015) and sediment (Tsui et al, 2015) can reach up to 1770.3 ng/L and 64.5 ng/g dry weight (dw), respectively, with an overall high level of contamination. In addition, OUVFs usually have high octanol-water partition coefficients (logKow = 4-8), which are prone to accumulate in the body and produce various toxic effects after ingestion by aquatic organisms (Zhou et al, 2022b). Ma et al (2017) found a significant decrease in acetylcholinesterase (AChE) and catalase activities and a significant increase in superoxide dismutase and glutathione reductase activities in crucian carp (Carassius auratus) after 28 days of exposure to BM-DBM, indicating an impairment of the nervous system and antioxidant defense system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cell permeability of gills, in direct contact with the surrounding medium, can act as a protective barrier against xenobiotics. This could reduce pollutant accumulation through the direct route 32 . We observed through the waterborne exposure a strong production of mucus coming out from the clams' valves which could also act as a protective mechanism of gills towards contamination by trapping NPs and rejecting them into the surrounding medium.…”
Section: Differences Between Gills and Visceral Massmentioning
confidence: 99%